2016
DOI: 10.31989/ffhd.v6i7.272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kefir on Fusobacterium nucleatum Potentially Causing Intestinal Cancer

Abstract: Background: Fusobacterium spp. are known to be part of mouth and intestinal microbiota. Fusobacterium nucleatum is an obligate anaerobe, Gram negative, non-spore forming pleomorphic bacillus that can cause diseases not only in the mouth and teeth but also in the brain, pleura, lungs and liver. It was noted that F. nucleatum induces fetal death (fetal demise) in pregnant women. Recent studies indicate that F. nucleatum could lead to colon cancer by binding to the epithelial tissue. Kefir is produced from kefir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Fusobacteria comprises gramnegative, nonsporulating, obligate anaerobic bacilli. A recent study reported in vitro antimicrobial activity of kefir against Fusobacterium nucleatum, a well-known member of phylum Fusobacteria (Guzel-Seydim et al, 2016). In parallel, we reported a negative interaction between kefir and intestinal phylum Fusobacteria and family Fusobacteriaceae in vivo, more specifically with Fb.…”
Section: Discussionsupporting
confidence: 74%
“…Fusobacteria comprises gramnegative, nonsporulating, obligate anaerobic bacilli. A recent study reported in vitro antimicrobial activity of kefir against Fusobacterium nucleatum, a well-known member of phylum Fusobacteria (Guzel-Seydim et al, 2016). In parallel, we reported a negative interaction between kefir and intestinal phylum Fusobacteria and family Fusobacteriaceae in vivo, more specifically with Fb.…”
Section: Discussionsupporting
confidence: 74%
“…The potential use of strains from the fermented milk, kefir, to inhibit F. nucleatum in vitro has also been noted. 39 Recently, in a study which screened the athlete gut microbiome for antimicrobial-producers, two bacteriocin-producing strains of Enterococcus faecalis were isolated which demonstrated anti -F . nucleatum activity in lab media.…”
Section: Discussionmentioning
confidence: 99%
“…The notable positive effects of kefir on cancer cell lines encourage its consumption as a functional diet in cancer prevention, especially in the case of intestinal cancer [88] and colorectal cancer [79]. Nevertheless, it should be noted that such evidence still lacks clinical trials and is mostly based on cell culture-based assays.…”
Section: Anticancer Activitymentioning
confidence: 99%